Derecho a la educación del tercer nivel y su inaplicabilidad en la realidad social. - Velasco Tandazo, Linda Verónica (2015)
Ecuador 's Constitution guarantees equal opportunities in access to higher education and for free , also the leveling and admission procedure is defined in the Law on Higher Education.